Effects of feeder design and feeder adjustment on the growth performance of growing- finishing pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two experiments were performed to evaluate the effects of feeder design (conventional dry feeder vs. wet-dry feeder) and adjustment on growing-finishing pig performance. In both experiments, all pigs (PIC 337 × 1050) were fed the same corn-soybean meal diets with 15% dried distillers grains with solubles (DDGS). In Exp. 1, 1,296 pigs (initially 43 lb) were used in a 69-d study. From d 0 to 27, 3 feeder settings were evaluated for each feeder type. Numbered settings (located in each feeder) were 6, 8, and 10 for the conventional dry feeder and 6, 10, and 14 for the wet-dry feeder. An increased setting number corresponded to a greater opening. From d 27 to 69, all feeders were adjusted to an opening of approximately 1 in. (conventional dry feeder setting 8; wet-dry feeder setting 14). From d 0 to 27, pigs using a wet-dry feeder had lower (P < 0.02) ADFI and better F/G than pigs using a conventional dry feeder. Increasing the feeder setting improved (linear, P < 0.01) ADG, ADFI, and d-27 BW of pigs using a wet-dry feeder and increased (linear, P < 0.01) ADFI of pigs using a conventional dry feeder. From d 27 to 69, ADG and ADFI of pigs using a wet-dry feeder were greater (P < 0.01) than those of pigs using a conventional dry feeder, and increasing the feeder setting from d 0 to 27 resulted in greater (linear, P < 0.01) ADFI and poorer F/G for pigs using a wet-dry feeder. Overall (d 0 to 69), pigs using a wet-dry feeder had greater (P < 0.05) ADG, ADFI, final BW, and better F/G than pigs that used a conventional dry feeder. Increasing the feeder setting of a wet-dry feeder from d 0 to 27 resulted in greater (linear, P < 0.01) ADG and ADFI, poorer (linear, P < 0.03) F/G, and heavier (linear, P < 0.01) final BW. Feeder setting of a conventional dry feeder from d 0 to 27 did not affect overall performance. In Exp. 2, 1,248 pigs (initially 73 lb) were used in a 93-d study. Three feeder settings were evaluated throughout the study for each feeder type (conventional dry feeder set at 6, 8, and 10; wet-dry feeder set at 10, 14, and 18). Overall, pigs using a wet-dry feeder had greater (P < 0.05) ADG, ADFI, final BW, HCW, backfat depth, and feed cost but reduced (P < 0.04) fat-free lean index (FFLI) compared with pigs using a conventional dry feeder. Increasing the feeder setting of a wet-dry feeder resulted in greater (linear, P < 0.05) ADG, ADFI, final BW, HCW, backfat depth, and feed cost. When HCW was used as a covariate, FFLI of pigs using a wet-dry feeder decreased (linear, P < 0.02) with increased feeder opening. Increasing the feeder setting of a conventional dry feeder had no effect on growth performance and carcass characteristics. In conclusion, the growth rate of pigs improved with a wet-dry feeder compared with a conventional dry feeder; however, the growth of pigs using a wet-dry feeder was more sensitive to differences in feeder adjustment.
Keywords: Swine; Conventional feeder; Feeder adjustment; Wet-dry feeder